2007
DOI: 10.1002/adsc.200600499
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Enantiopure (S,R,S)‐ and (R,S,R)‐1,4,5,8,9,16‐Hexahydroxytetraphenylenes

Abstract: Scheme 3. Synthesis of racemic 5 from 11. a) PhIA C H T U N G T R E N N U N G (OAc) 2 , CH 3 CN, H 2 O, 0 8C, 2 h, 48 % for 12, 22 % for 13; b) Zn, AcOH, room temperature, 7 h, 74 %; c) BBr 3 , CH 2 Cl 2 , 08C to room temperature, 12 h, 90 %.Scheme 4. Synthesis of (S,R,S)-5. a) CH 3 I, K 2 CO 3 , acetone, reflux, 3 h, 100 %; b) i) 2.2 equivs. BBr 3 , CH 2 Cl 2 , 08C, 15 min; ii) 2.2 equivs. Tf 2 O, pyridine, CH 2 Cl 2 , 10 h, 27 %; c) NaOH, dioxane, methanol, 60 8C, 12 h, 98 %; d) i) PhIA C H T U N G T R E N N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…[2] Such flexible redox behavior is one of the significant characteristics of COTs, particularly those constructed from five-membered heteroaromatics where tub-to-plane interconversion of the saddle-shaped skeleton is sufficiently facilitated. [4] Owing to the unique structural and electronic properties of this class of compounds,t here exist potential applications in various fields,i ncluding asymmetric synthesis [5] and supramolecular chemistry. [4] Owing to the unique structural and electronic properties of this class of compounds,t here exist potential applications in various fields,i ncluding asymmetric synthesis [5] and supramolecular chemistry.…”
mentioning
confidence: 99%
“…[2] Such flexible redox behavior is one of the significant characteristics of COTs, particularly those constructed from five-membered heteroaromatics where tub-to-plane interconversion of the saddle-shaped skeleton is sufficiently facilitated. [4] Owing to the unique structural and electronic properties of this class of compounds,t here exist potential applications in various fields,i ncluding asymmetric synthesis [5] and supramolecular chemistry. [4] Owing to the unique structural and electronic properties of this class of compounds,t here exist potential applications in various fields,i ncluding asymmetric synthesis [5] and supramolecular chemistry.…”
mentioning
confidence: 99%
“…Compounds 3, 4, and 7 form centrosymmetric dimers of adjacent molecules in the solid state by p-p-interactions between one cyclopentadienyl and one phenyl (3), two cyclopentadienyl (4), or two phenyl rings (7). Geometrical details given in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Nickel phosphanes have attracted considerable interest in recent years because they can be applied successfully in homogeneous catalysis including the polymerization of formaldehyde [1,2], dimerization of propene [3][4][5][6][7][8][9][10][11], synthesis of a-olefines [12][13][14][15][16][17][18][19], asymmetric hydrocyanation of styrene [20,21], hydrogenolysis of biphenylene [22,23], and the coupling of Grignard reagents with chloropyrimidines [24,25] and aryl chlorides [26,27]. Due to their diverse applications in the field of material sciences, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, conversion of racemic tetrahydroxytetraphenylene 58 into its tetra-(S)-camphorsulfonate esters after esterification with (S)-camphorsulfonyl chloride resulted in two diastereomers (132a and 132b). Chromatographic separation and subsequent deprotection afforded enantiopure 1,8,9,16-tetrahydroxyltetraphenylene (58) [79,80]. The presence of hydroxyl groups in the tetraphenylene skeleton has provided openings for further chemistry through late functional group transformations.…”
Section: Late Functionalization Of Tetraphenylene Derivativesmentioning
confidence: 99%
“…4) [80]. To have a better understanding of the structures of 138-140, the results of density functional theory computation showed that their structures all seemed to be rod-like chains.…”
Section: Late Functionalization Of Tetraphenylene Derivativesmentioning
confidence: 99%